The effects of obesity and HER‐2 polymorphisms as risk factors for endometrial cancer in Korean women - Tong, S‐Y; Ha, S‐Y; Ki, K‐D; Lee, J‐M; Lee, S‐K; Lee, K‐B; Kim, M‐K; Cho, C‐H; Kwon, S‐Y (BJOG : an international journal of obstetrics and gynaecology, 2009)
Objective  To evaluate the relationship between single nucleotide polymorphisms (SNPs) in the HER‐2 gene, body mass index (BMI) and the risk of endometrial cancer. Design  Case–control study. Setting  Medical centres in Korea. Sample  DNA samples and medical histories were obtained from 125 endometrial cancer cases and 302 controls. Methods  The genotypes evaluated in HER‐2 at positions –423, –655, –776, –857, –1170, –1177, –1253 of the coding region and two SNPs located in an intron by SNP‐IT assay using SNPstream Ultra–high throughput system. Main outcome measures  Odd ratio for endometrial cancer associated with HER‐2 polymorphisms and BMI. Results  Cases had a significantly higher BMI than controls and the obese subjects had a 2.65‐fold increased risk for endometrial cancer. However, HER‐2 polymorphism was not associated significantly with the risk of endometrial cancer. Subjects with BMI ≥ 25 kg/m2 who carried rs1801200 AA, rs1801200 GA/GG, rs1810132 CT/CC, rs2517951 CT/TT and rs1058808 CG/GG genotype had significantly increased risk of endometrial cancer than subjects with a normal BMI (P for linear trend <0.05). However, the risk in the subjects with the variant allele for HER‐2 genotypes did not differ significantly compared to those with homozygous wild‐type allele within specific BMI subgroups. Conclusions  Endometrial cancer risk increased significantly in proportion to BMI. However, HER‐2 polymorphism did not affect significantly on the risk of endometrial cancer.